Utility of kinetic and kinematic jumping and landing variables as predictors of injury risk: a systematic review - Pedley, J. S.; Lloyd, R. S.; Read, P. J.; Moore, I. S.; Croix, M. D. S.; Myer, G. D.; Oliver, J. L. (Journal of Science in Sport and Exercise, 2020)
Purpose: Jump-landing assessments provide a means to quantify an individual`s ability to attenuate ground reaction forces, generate lower limb explosive power and maintain joint alignment. In order to identify risk factors that can be targeted through appropriate training interventions, it is necessary to establish which (scalar) objective kinetic, kinematic, and performance measures are most associated with lower-extremity injury. Methods: Online searches of MEDLINE, SCOPUS, EBSCOHost, SPORTDiscus and PubMed databases were completed for all articles published before March 2020 in accordance with PRISMA guidelines. Results: 40 articles investigating nine jump-landing assessments were included in this review. The 79% of studies using drop jump (n = 14) observed an association with future injury, while only 8% of countermovement jump studies (n = 13) observed an association with injury risk. The 57% of studies using unilateral assessments found associations with risk of injury (n = 14). Studies using performance measures (jump height/distance) as outcome measure were only associated with injury risk in 30% of cases. However, those using kinetic and/or kinematic analyses (knee abduction moment, knee valgus angle, knee separation distance, peak ground reaction force) found associations with injury in 89% of studies. Conclusion: The landing element of jump-landing assessments appears to be superior for identifying individuals at greater risk of injury; likely due to a closer representation of the injury mechanism. Consequently, jump-landing assessments that involve attenuation of impact forces such as the drop jump appear most suited for this purpose but should involve assessment of frontal plane knee motion and ground reaction forces.